Greater Breast Support Is Associated With Reduced Oxygen Consumption and Greater Running Economy During a Treadmill Running Task - Fong, Hailey B.; Powell, Douglas W. (Frontiers in Sports and Active Living, 2022)
Introduction Breast pain is a major barrier to running for women. While breast support through the use of sports bras reduces breast-related discomfort, the effect of breast support on running performance is less understood. Therefore, the purpose of the current study was to evaluate the effect of greater breast support on oxygen consumption and running economy during a treadmill running task. Methods Fifteen female recreational runners performed a 10-min treadmill running task at their preferred running speed in each of two sports bra conditions: low support and high support. Participants ran on an instrumented treadmill (1,200 Hz, Bertec) while indirect calorimetry was performed using a metabolic measurement system (100 Hz, TrueOne, ParvoMedics). Average VO2 (absolute and relative) from the third to 10th minutes was used to evaluate oxygen consumption. Running economy was calculated as the distance traveled per liter of oxygen consumed. Paired samples t-tests were used to compare mean oxygen consumption and running economy values between breast support conditions. Correlation analysis was performed to evaluate the relationship between breast size and change in running performance. Results Greater breast support was associated with reductions in absolute (p < 0.001) and relative oxygen consumption (p < 0.001; LOW: 30.9 ± 7.1 ml/kg/min; HIGH: 28.7 ± 6.7 ml/kg/min). Greater breast support was associated with increases in running economy (p < 0.001; LOW: 88.6 ± 29.1 m/L O2; HIGH: 95.2 ± 31.1 m/L O2). No changes in temporospatial characteristics of running were observed including cadence (p = 0.149), step length (p = 0.300) or ground contact time (p = 0.151). Strong positive linear correlations were observed between the change in running performance metrics and breast size (Oxygen Consumption: p < 0.001, r = 0.770; Relative Oxygen Consumption: p < 0.001, r = 0769; Running Economy: p < 0.001, r = 0.807). Conclusions Greater breast support was associated with reduced oxygen consumption and increased running economy. These findings demonstrate that greater breast support is not only associated with improved comfort but also improved running performance.